2021
DOI: 10.1093/nar/gkab792
|View full text |Cite
|
Sign up to set email alerts
|

Optimized nickase- and nuclease-based prime editing in human and mouse cells

Abstract: Precise genomic modification using prime editing (PE) holds enormous potential for research and clinical applications. In this study, we generated all-in-one prime editing (PEA1) constructs that carry all the components required for PE, along with a selection marker. We tested these constructs (with selection) in HEK293T, K562, HeLa and mouse embryonic stem (ES) cells. We discovered that PE efficiency in HEK293T cells was much higher than previously observed, reaching up to 95% (mean 67%). The efficiency in K5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…The pAIO-PE3 plasmid, combined with a puromycin selection showed a significant increase compared to the regular PE3 system in mouse stem embryonic stem cells, with edit efficiencies ranging between 1.7% and 85%. In line with other ncRNA-dependent PE systems, pAIO-PE3 activity however also resulted in a high rate of indel/SNVgeneration for most loci, occurring in up to 90% of the clones [6] . Since PE3 systems are accompanied by higher undesired indels/SNVs, improved versions of ncRNA-independent PE systems would be safer alternatives for gene-editing in iPSC-derived models.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…The pAIO-PE3 plasmid, combined with a puromycin selection showed a significant increase compared to the regular PE3 system in mouse stem embryonic stem cells, with edit efficiencies ranging between 1.7% and 85%. In line with other ncRNA-dependent PE systems, pAIO-PE3 activity however also resulted in a high rate of indel/SNVgeneration for most loci, occurring in up to 90% of the clones [6] . Since PE3 systems are accompanied by higher undesired indels/SNVs, improved versions of ncRNA-independent PE systems would be safer alternatives for gene-editing in iPSC-derived models.…”
Section: Introductionsupporting
confidence: 70%
“…The few studies that tested multi-plasmid PE3 for editing in hiPSC showed a nearly undetectable edit efficiency [4] , making it not suitable for the generation of iPSC-derived disease models. However, the recently published PEA1 (pAIO-PE3) all-in-one plasmid was able to increase the edit efficiency significantly in immortalized cell lines as well as mouse embryonic stem cells (mESC) when combined with a puromycin selection step [6] . It did however induce similarly high unintended alterations as seen in the multi-plasmid approach.…”
Section: Pe4max and The Advantage Of Specific Base Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy yielded the PE4 (PE2 + MLH1dn), PE5 (PE3 + MLH1dn), and PE5b (PE3b + MLH1dn) editors 7 . In addition, nuclease prime editors have been shown to improve PE efficiency, but it comes at the expense of product purity 10 – 12 . Thus, the optimal PE strategy to adopt varies according to the context and there is a need to develop methods to consistently improve its success rate.…”
Section: Introductionmentioning
confidence: 99%
“…We considered whether enrichment of genomic editing was caused by higher co-transfection rates of all prime editing plasmids in fluoPEER-edited cells 23 . We therefore transfected a mix of up to four fluorescent plasmids (mTurq2, eGFP, mKO2, mCherry) and tested co-transfection efficiency using FACS.…”
Section: Resultsmentioning
confidence: 99%